Effect of interactive intensity on lexical alignment and L2 writing quality. (August 2022) - Wang, Min; Gan, Qiao; Boland, Julie E.
Abstract: This study examined the relationships among interactive intensity, lexical alignment and L2 writing quality under two variations (multi-turn vs. single-turn) of a story continuation task. The multi-turn version entailed more interaction between the learner and the text than the single-turn version. One-hundred and nine Chinese undergraduates were assigned to either the multi- or the single-turn group. The continuation task was preceded by a pretest one week earlier and followed by a posttest two weeks later. Both versions of the continuation task resulted in lexical alignment but the magnitude was stronger in the multi-turn mode. Compared with the pretest, participants' use of content and function words was more similar to the input when completing the story and during the posttest, and increases in the similarity of content words were more marked in the multi-turn group. Furthermore, the effect of alignment on writing quality was influenced by interactive intensity: the multi-turn group improved more remarkably from the pretest to the posttest than the single-turn group. By employing the algorithmic indices Latent Semantic Similarity (LSS) and Language Style Matching (LSM), this study was the first to examine L2 lexical alignment beyond exact repetition of content words and the first to associate interactive intensity with L2 writing quality.